FACTORS ASSOCIATED WITH MEDICATION ADHERENCE IN PATIENTS WITH TUBERCULOSIS YEAR 2024 - Marlena Hartati; Rita Ramayulis; Prihayati (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
Tuberculosis (TB) is an infectious disease caused by the Mycobacterium Tuberculosis (MTB) germ. Tuberculosis is transmitted through the air from infectious tuberculosis patients to those around them. One bacteriologically confirmed tuberculosis patient who is not properly and qualitatively treated can infect about 10 people per year (Ministry of Internal Affairs RI, 2019). Banten is one of the provinces with a high number of tuberculosis sufferers on the island of Java. According to the Ministry of Internal Affairs of RI in 2019, 223 people were infected with tuberculosis per 100,000 inhabitants, above the national average of 203 people per 100,000 population (Kemenkes RI, 2019). However, of the total number of Tuberculosis sufferers in Banten Province, only 58.3% take the drug regularly (Kemenkes RI, 2018). The causative factors of the disease include nutritional status, age, gender, environmental factors, and social factors. This type of study is an analytical study with a cross-sectional study design. to 52 samples. The results of the Chi Square test show that there is a meaningful relationship between age, level of knowledge, attitude to treatment, history of drug side effects, role of health care workers, access to health services, and family support with the level of drug adherence in TB patients.